Hibla - Viva Films ([Quezon City] Viva Films, 2003)
Hibla is the story of two childhood friends named Isabel (Rica Peralejo) and Clara (Maui Taylor) from a small town who were seperated when Clara's family moved to the city due to her mother's ambition. Isabel has since learned to live without her best friend and continued living her simple life with her boyfriend Lando (Antonio Aquitania) who loves her but is frustrated by her conservatism and idealism. Clara's father (Ricky Davao) decides to bring her back to the town to start a new life. As each of them seek their own idea of fulfillment, their motivations and actions will lead them to a tragic and inevitable end.
DVD
Edgar Ilaw, Quark Henares, Yam Laranas, screenplay ; executive producer, Vic Del Rosario Jr., directed by Yam Laranas
Rica Peralejo, Maui Taylor, Ricky Davao, Antonio Aquitania
Keywords: Feature films